Optical Bullets and Domain Walls with Cross Spatio-Dispersion and Having Kudryashov’s form of Self-Phase Modulation (Contemporary Mathematics, 2023)
In this paper, we investigate the retrieval of optical bullets and domain walls in a novel context, considering the interplay of cross spatio-dispersive effects and employing Kudryashov' s proposed form of self-phase modulation. The integration of these two key elements represents a significant advancement in the field of nonlinear optics, enabling the recovery of optical structures with enhanced precision and control. We propose an enhanced Kudryashov’s approach, which overcomes the limitations of conventional methods and facilitates the retrieval of optical bullets and domain walls even in the presence of cross spatio-dispersive effects. Kudryashov' s self-phase modulation mechanism has proven to be a powerful tool in controlling the nonlinear dynamics of optical systems, offering unique opportunities to manipulate light waves through phase variations induced by the medium' s response to intense optical fields. The results presented herein offer new insights into the intricate interplay between self-phase modulation and spatio-dispersive effects in nonlinear optical systems. Moreover, our findings provide a promising avenue for developing novel applications in ultrafast all-optical signal processing, such as the manipulation of light bullets for high-speed data transmission and storage. The enhanced retrieval and control of optical bullets and domain walls are expected to have a profound impact on the advancement of nonlinear optics and its practical implications.
Keywords: bullets, Kudryashov, cross spatio-dispersion, domain walls